ANALYSIS AND PROSPECTS OF PRIVATE PENSION FUNDS IN RUSSIA - A. Pudovkin (Vestnik MGIMO-Universiteta)
The article under the title "Analysis and prospects of private pension funds in Russia" deals with the pension system of the Russian Federation and the problems that the private pension funds will be facing with the introduction of the new pension reform. In addition, the article also deeply studies the private pension funds market in Russia. The study presented in the article also aims to thoroughly analyze the key drivers of the recent boom of the private pension funds sector. In addition, the study also reflects on the prospects of development of private pension funds and the major growth factors for the future taking into considerations the latest pension reform. It is exactly the pension capital that constitutes the major role to the growth of the the private pension funds market. In addition, taking into account the latest developments in the pension legislature, which imply no pension capital available to the private pension funds for the period 2014-2015 years, it is easy to foresee that the only growth factor left is pension reserves. Overall it obviously means that private pension funds should develop private pension schemes. Moreover, private pension insurance may become the major driver of the whole pension industry in the near future.